2022
DOI: 10.31234/osf.io/jr6m4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential influence of habit components on compulsive and problematic reward-seeking behavior

Abstract: Habitual behavior has been identified as a key process involved in a variety of mental health disorders. Previous research has shown that habit is not a unitary construct. The present study examined how different components of habitual behavior relate to problematic reward-seeking behaviors and compulsive behaviors. Four hundred and one participants completed a French version of the Creature of Habit Scale, which measures two components of habitual behavior: routine and automaticity. Participants also complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Second, OCD patients self-reported greater habitual tendencies in both the ‘routine’ and ‘automaticity’ subscales. Previous studies have reported that subjective habitual tendencies are associated with compulsive traits ( Ersche et al, 2019 ; Wuensch et al, 2022 ) and act, in addition to cognitive inflexibility, as a predictor of subclinical OCD symptomatology in healthy populations ( Ramakrishnan et al, 2022 ). There is an apparent discrepancy between self-reported ‘automaticity’ and the objective measure of automaticity we provided.…”
Section: Discussionmentioning
confidence: 99%
“…Second, OCD patients self-reported greater habitual tendencies in both the ‘routine’ and ‘automaticity’ subscales. Previous studies have reported that subjective habitual tendencies are associated with compulsive traits ( Ersche et al, 2019 ; Wuensch et al, 2022 ) and act, in addition to cognitive inflexibility, as a predictor of subclinical OCD symptomatology in healthy populations ( Ramakrishnan et al, 2022 ). There is an apparent discrepancy between self-reported ‘automaticity’ and the objective measure of automaticity we provided.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, OCD patients self-reported greater habitual tendencies in both the ‘routine’ and ‘automaticity’ subscales. Previous studies have reported that subjective habitual tendencies are associated with compulsive traits (Ersche et al, 2019; Wuensch et al, 2022) and act, in addition to cognitive inflexibility, as a predictor of subclinical OCD symptomatology in healthy populations (Ramakrishnan et al, 2022). There is an apparent discrepancy between self-reported ‘automaticity’ and the objective measure of automaticity we provided.…”
Section: Discussionmentioning
confidence: 99%